Implementasi Kebijakan Joko Widodo Melalui Program KJS dan KJP (Ditinjau dari Perspektif Komunikasi Pembangunan) - Indah Suryawati (Program Studi Ilmu Komunikasi, 2014)
This study aims to analyze the implementation of Joko Widodo`s policy of Kartu Jakarta Sehat (KJS) and Kartu Jakarta Pintar (KJP) programs. This research is to show the opinion from poor people of Jakarta related with KJS and KJP implementation based on the perspective of development communication. This research method is descriptive qualitative. Collection of primary data obtained through in depth interviews of the poor public in Jakarta related KJS and KJP programs. Meanwhile, collection of secondary data obtained through documentation of the various media and library research. The conclusion of this research explains Jokowi`s poverty alleviation policies has not fully implementation.